Lumbar Subarachnoid Neurocysticercosis: A Case Report with Literature Review - Chandrakanth, Kanakam; G., Krishna Kumar; Reddy, Ravi Suman; Multani, Kartik Manoj (Indian Journal of Neurosurgery, 2021)
Neurocysticercosis (NCC) is the most common parasitic infection of brain. Spinal NCC is commonly seen in association with cranial lesions. However, they do present rarely as isolated spinal lesions. Spinal NCC may present with vague symptoms, pain, paraparesis or, sometimes as, cauda equina syndrome. Spinal NCC with neurological deficits is an emergency, and it should be operated immediately followed by antiparasitic medications. We report a primary lumbar NCC patient, who presented with radicular pain. She underwent complete excision of cyst.
Keywords: lumbar IDEM; spinal neurocysticercosis; lumbar cyst